Effect of Chemical Pesticides on the Growth and Yield of Two Industrial Potato Varieties (Asterix and Courage) in Bangladesh - Hoque, Md Azizul; Sikder, Md Maniruzzaman; Khair, Abul (Journal of Bio-Science, 2024)
Experiments were conducted to find out suitable disease management practices to produce quality potato seeds in processing the varieties of Asterix and Courage in Bangladesh. A set of two field experiments was conducted in two different Agroecological zones of Bangladesh. A Factorial Randomized Completely Block Design with 2 potato varieties, 4 treatments, and 4 replications for each were used. A significant difference was found in the plant height and number of tubers per hill. In contrast, days to tuberization and the number of stems per hill of both varieties in response to pesticide application were insignificant. The highest tuber yield and better A and B-grade tubers were recorded, in which fungicides and insecticides were applied. The primary viral infection had been identified in the control and fungicide-treated plots only while there was no viral disease incidence was observed in the insecticide-treated plots. The incidence of post-harvest disease and disorder was found to be negligible. J. Bio-Sci. 32(2): 13-22, 2024